Da'wah Strategy through Islamic Education in the Digital Era - Rahwan Rahwan; Hosaini Hosaini; Muharofah Nur Safitri; Muzammil Muzammil (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2026)
The digital revolution has fundamentally reshaped how religious values are communicated, yet Islamic education institutions have been slow to adapt their da'wah (preaching) strategies accordingly. This study addresses this gap by identifying and analyzing effective digital da'wah strategies within the context of Islamic education in Indonesia, the world's largest Muslim-majority country. Employing a qualitative literature review methodology with descriptive analysis, the research systematically examines academic articles, books, and policy documents published between 2015 and 2025. Through iterative processes of data reduction, thematic categorization, and interpretive analysis, four strategic pillars emerge: (1) integration of technology-based curricula, (2) utilization of social media as a religious education medium, (3) development of online learning platforms, and (4) strengthening digital literacy among educators and students. These strategies collectively expand da'wah reach, enhance youth engagement, and deepen the internalization of Islamic values in digital spaces. The study makes two significant contributions: theoretically, it advances digital da'wah discourse by foregrounding its adaptive and contextual dimensions within Islamic education; practically, it offers actionable recommendations for institutional policy reform, educator capacity building, and ethical digital content production. Future research should employ empirical methods including surveys, experiments, and longitudinal studies to assess the effectiveness, challenges, and long-term impacts of digital da'wah on religious behavior and social transformation across diverse Muslim communities.